O exame neurológico do recém-nascido pré-termo não complicado: avaliação pela escala de saint-anne dargassies, e screening pelas escalas de amiel-barrier-shnider modificada e prechtl ao termo - Alves, Carla Ismirna Santos (2010)
This study compared the evolution of posture, tone and neonatal reflexes in preterm infants without clinical or neurological complications before and after the age of term using the scale of Saint-Anne Dargassies. To reach the age of the term, was applied Scales Amiel-Barrier-Shnider changed and the Prechtl, traditionally used in the evaluation of term newborns, looking for possible changes to the term, while also evaluating the sensitivity of these scales. We studied 20 non-complicated preterm infants, both sexes aged 32-36 weeks, born in Januário Cicco Maternity School, from August 2006 to August 2007. Was applied to the scale of Saint-Anne Dargassies every two weeks until reach the term, and the range of Amiel-Barrier-Shnider changed and the Prechtl, after reaching 39 and 41 weeks. The evaluation result of articular angles was subjected to the test of Friedman ANOVA, significant differences between the three measurements of the scale of Saint-Anne Dargassies only for angles heel-to-ear to term. Neonatal reflexes changed in the period of prematurity were the cardinal points reflexes, Moro reflexes, cross extensions reflex and the automatic walking reflexes. The posture was the parameter which remained unchanged in the three scales. Considering a significance level of 5% by applying Cochran Q Test, it was found that the scale of Saint-Anne Dargassies is more sensitive to detect suspects. With this methodology and the results it was possible to prepare a manuscript: The neurological examination of non-complicated preterm newborns using the Sanit-Anne Dargssies Scale from birth to term: normal or altered? In which we describe that despite the good clinical condition, the RNP show changes in tone and neonatal reflexes. These data are important because though non-complicated RNP need further attention its maturation process, enabling us to detect and intervene early. With these results we can build a scale simplified neurological assessment made with items found most altered during the application of three scales. The development of this project has a multidisciplinary approach, because it involved Paediatric Neurologist, Physiotherapist and Neonatologist, as recommended by PPGCSA